(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Laparoscopic cholecystectomy is the most common for the treatment of calculous cholecystitis, especially in elderly patients. However, the assessment of the time of intervention to treat calculous cholecystitis at the time before and after 72 hours from the onset of the disease has not been paid enough attention. Methods: A prospective descriptive study of a series of elderly patients (aged 60 years and older) diagnosed calculous cholecystitis and had laparoscopic cholecystectomy at Nguyen Tri Phuong Hospital from March 2023 to August 2023. Patients were divided into 2 groups according to the time from symptom onset to surgery: group I (surgery before 72 h) & group II (surgery after 72 h) Results: There were 32 patients included in the study. The male/female ratio is 2/3; average 69.5 ± 8.1 years old; There was no difference in age and sex between the 2 groups. The prominent clinical symptoms are abdominal pain (100%), fever (68.8%). During surgery, group I observed less adhesion inflammation in the hepatobiliary triangle compared with group II (p<0.05). 6 case of intraoperative complication in group II. The surgical results of group I were better than those of group II (p < 0.05), the rate of good surgical results was 78.1%, the average level was 21.9%. Conclusion: Laparoscopic cholecystectomy for the treatment of calculous cholecystitis in the elderly showed positive results. Surgery within the first 72 hours of symptoms shows better results.